2017
DOI: 10.1111/febs.14180
|View full text |Cite
|
Sign up to set email alerts
|

13C metabolic flux profiling of Pichia pastoris grown in aerobic batch cultures on glucose revealed high relative anabolic use of TCA cycle and limited incorporation of provided precursors of branched‐chain amino acids

Abstract: Acetohydroxy acid isomeroreductase (EC 1.1.1.86), branched-chain amino acid aminotransferase (BCAT, EC 2.6.1.42), fumarase (EC 4.2.1.2), malic enzyme (EC 1.1.1.39/1.1.1.40), phosphoenolpyruvate carboxykinase (EC 4.1.1.49), pyruvate carboxylase (EC 6.4.1.1), pyruvate kinase (EC 2.7.1.40), l-serine hydroxymethyltransferase (EC 2.1.2.1), threonine aldolase (EC 4.1.2.5), threonine dehydratase (EC 4.3.1.19); transketolase (EC 2.2.1.1), transaldolase (EC 2.2.1.2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
(193 reference statements)
1
5
0
Order By: Relevance
“…The directionality of the mitochondrial malate dehydrogenase was fixed in the direction of malate oxidation, consistent with an inactive glyoxylate cycle under various carbon sources (Sola et al., 2004, 2007) and more recent 13C flux data in aerobic, glucose-limited cultures (Sola et al., 2004; Zhang et al., 2017). Finally, the activity of the malic enzyme was blocked as it carries a neglectable flux under the hypoxic and normoxic conditions in glucose-limited cell cultures (Baumann et al., 2010; Zhang et al., 2017). Altogether, correction of these reactions substantially improved mitochondrial flux predictions, as compared to available 13C flux measurements (see below).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The directionality of the mitochondrial malate dehydrogenase was fixed in the direction of malate oxidation, consistent with an inactive glyoxylate cycle under various carbon sources (Sola et al., 2004, 2007) and more recent 13C flux data in aerobic, glucose-limited cultures (Sola et al., 2004; Zhang et al., 2017). Finally, the activity of the malic enzyme was blocked as it carries a neglectable flux under the hypoxic and normoxic conditions in glucose-limited cell cultures (Baumann et al., 2010; Zhang et al., 2017). Altogether, correction of these reactions substantially improved mitochondrial flux predictions, as compared to available 13C flux measurements (see below).…”
Section: Resultssupporting
confidence: 83%
“…Integration of transcriptomic and proteomic data under appropriate experimental conditions (Clasquin et al., 2011; Gasser et al., 2007; Rußmayer et al., 2015; Zhang et al., 2017), and directionalities based on reaction thermodynamics, reduced the number of reversible reactions by 25 and blocked 23 initially active reactions (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology has driven developments such as methyl-TROSY, , thereby opening the NMR approach to ever larger complexes. , Evaluation of the selected methyl incorporation has thereby mostly been done under conditions of protein overexpression, whereby the bacterial metabolism becomes massively geared toward the biosynthesis of the desired protein. However, recently, it was shown that the Pichia pastoris yeast cells consume a larger fraction of the 2-oxobutanoate (2OB) precursor when protein expression is induced . It is thus interesting to test to what extent this precursor is imported or neo-synthesized when bacteria are grown without any protein overexpression.…”
Section: Results and Discussionmentioning
confidence: 99%
“…We have extended this work by demonstrating the 13 C, 1 H labeling of isoleucine δ1-methyl groups in a perdeuterated background by adding labeled α-ketobutyrate (~50% labeling, ~90% deuteration) to highly deuterated growth media (Clark, Dikiy, Chapman, Rodstrom, Aramini, LeVine et al, 2017;Clark, Zahm, Ali, Kukula, Bian, Patrie et al, 2015). In contrast, simultaneous labeling of leucine δand valine γ-methyl groups with αketoisovalerate is inefficient but can be achieved by adding labeled valine directly to the growth media or modifying culture conditions (Clark et al, 2015;Suzuki, Sakakura, Mori, Fujii, Akashi, & Takahashi, 2018;Zhang, Yu, Xu, Jouhten, Swapna, Glaser et al, 2017). Pichia can readily take up additional amino acids from media, with a general correlation between uptake efficiency and the energetic cost to synthesize that amino acid type de novo (Heyland, Fu, Blank, & Schmid, 2011).…”
Section: Introductionmentioning
confidence: 98%